활동 궤양성 대장염 환자에서 발생한 폐혈전색전증 1예 - 박병도; Byoung Do Park; 김형길; Hyung Gil Kim; 정현정; Hyun Jung Jung; 최용준; Yong Jun Choi; 김상구; Sang Gu Kim; 김수한; Soo Han Kim; et al. (The Korean journal of gastroenterology, 2009)
Inflammatory bowel disease often involves extra-intestinal organs. Cerebral thrombosis, portal vein thrombosis and pulmonary thrombosis have been reported. Deep vein thrombosis and pulmonary thromboembolism are significant causes of mortality in patients with inflammatory bowel disease. A 48-year-old woman was diagnosed as inflammatory bowel disease on colonoscopy and histology. We used hydrocortisone and mesalazine for the treatment of disease. Nineteen days later, she complained of abrupt dyspnea. Pulmonary CT angiography revealed a thromboembolism in right pulmonary arteries. After the treatment of heparin therapy, follow-up pulmonary CT angiography showed significant improvement of previously thrombosed pulmonary arteries. (Korean J Gastroenterol 2009;53:48-52)